(16+2x)(20+2x)=480

Simple and best practice solution for (16+2x)(20+2x)=480 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (16+2x)(20+2x)=480 equation:


Simplifying
(16 + 2x)(20 + 2x) = 480

Multiply (16 + 2x) * (20 + 2x)
(16(20 + 2x) + 2x * (20 + 2x)) = 480
((20 * 16 + 2x * 16) + 2x * (20 + 2x)) = 480
((320 + 32x) + 2x * (20 + 2x)) = 480
(320 + 32x + (20 * 2x + 2x * 2x)) = 480
(320 + 32x + (40x + 4x2)) = 480

Combine like terms: 32x + 40x = 72x
(320 + 72x + 4x2) = 480

Solving
320 + 72x + 4x2 = 480

Solving for variable 'x'.

Reorder the terms:
320 + -480 + 72x + 4x2 = 480 + -480

Combine like terms: 320 + -480 = -160
-160 + 72x + 4x2 = 480 + -480

Combine like terms: 480 + -480 = 0
-160 + 72x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-40 + 18x + x2) = 0

Factor a trinomial.
4((-20 + -1x)(2 + -1x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-20 + -1x)' equal to zero and attempt to solve: Simplifying -20 + -1x = 0 Solving -20 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -1x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -1x = 0 + 20 -1x = 0 + 20 Combine like terms: 0 + 20 = 20 -1x = 20 Divide each side by '-1'. x = -20 Simplifying x = -20

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Solution

x = {-20, 2}

See similar equations:

| (16+2x)(20+2x)=320 | | F=-4(c+3)+(6c-5)c | | -3(x-3)+x=8(9-x) | | E=2z(5+3z)-4 | | x(x-3)=x^2+8x+9 | | 4x+38=4 | | d=-2(y-8) | | x^4+12x=13x^2 | | 3*x+12=27 | | 4*x-4=36 | | c=5t-(t+8)+(t*t-2) | | 694+396+x=1742 | | y/13=34 | | 3x+4y=3.91 | | b=(b-4)-(5+3b) | | 2X=X(1+0.087) | | a=2-(5+2a) | | 14x^2+3x=0 | | 64x-4x^2=0 | | y=(-10x^2)+50X | | 3t^2/5=t/5+7/12 | | 2X=X(1+0.087)N | | x^2/6+5x/6+1=0 | | 1/4(x+12)=9 | | x^2-8x=x(5+x) | | 5(2+x)=4x+17 | | x^2+4x-24= | | 3x+3=10x-80 | | 2x^2+(3a+4b)x=0 | | 2x^2+(3a+4b)x+a^2+3ab+2b^2=0 | | 2(2c-1)=4(3c-2) | | 4b^2-11ab+6a^2=0 |

Equations solver categories